A Diabetic Gentleman with Fever and Abdominal pain - Das, Aparna; Islam, Shahidul; Kahhar, M Azizul (Journal of Bangladesh College of Physicians and Surgeons, 2017)
Abstract not available J Bangladesh Coll Phys Surg 2016; 34(3): 175-177